2021
DOI: 10.1155/2021/7781823
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic Mechanisms of Insulin Secretion and Signaling-Related Genes in Etiology of Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrinopathy in women. PCOS is characterized by anovulation, hyperandrogenism, polycystic ovaries, insulin resistance, and obesity. Despite the finding that the genetic origin of PCOS is well demonstrated in previous twin and familial clustering studies, genes and factors that can exactly explain the PCOS pathophysiology are not known. Objective(s). In this review, we attempted to identify genes related to secretion and signaling of insulin aspects of PCOS and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 98 publications
0
22
0
1
Order By: Relevance
“…The mild phenotype of this AS patient without IR or obesity, associated only with a mild initial increase of androgen levels, may have spared the patient's fertility and led to the possibility of a spontaneous conception. In fact, it is well known from PCOS studies that IR and hyperinsulinemia influenced fertility and conception, enhancing androstenedione and testosterone production, reducing SHBG levels, increasing free testosterone levels, stopping follicles growth, influencing pituitary gland sensitivity to GnRH, and stimulating pituitary LH release ( Shaaban et al, 2021 ). A recent study in mice suggests a direct role of ALMS1 on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The mild phenotype of this AS patient without IR or obesity, associated only with a mild initial increase of androgen levels, may have spared the patient's fertility and led to the possibility of a spontaneous conception. In fact, it is well known from PCOS studies that IR and hyperinsulinemia influenced fertility and conception, enhancing androstenedione and testosterone production, reducing SHBG levels, increasing free testosterone levels, stopping follicles growth, influencing pituitary gland sensitivity to GnRH, and stimulating pituitary LH release ( Shaaban et al, 2021 ). A recent study in mice suggests a direct role of ALMS1 on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity as a risk factor often causes female ~ 109 ~ diseases such as breast cancer [17] . Studies have found that, with increases in weight, abnormal genes such as the Wnt signaling pathway, oxidative stress, and inflammation in adipose tissue of PCOS patients are abnormal [18] , suggesting that obesity participates in the pathogenesis of PCOS [19] , triggers metabolic and reproductive disorders, and may also cause glycolipid metabolism, hyperandrogenaemia, menstrual disorders, infertility, and comorbidities related to polycystic ovary syndrome [20] . Furthermore, we also noticed that many features and complications of polycystic ovary syndrome (PCOS) can trigger oxidative stress and increase insulin resistance index [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…The genetic predisposition in PCOS is unquestionable and several genes are demonstrated to be involved in the etiology of the disease [ 25 ]. Indeed, due to the multifactorial nature of this disease, and to its polygenic contributions, it is not easy to offer a complete report about the genetic basis of PCOS [ 26 ].…”
Section: Mechanisms Involved In Pcos Pathogenesismentioning
confidence: 99%